The Influence of the Problem-Based Learning Model on Students' Ability to Understand Mathematical Concepts - Dewanti; Nursyam Anaguna; Aprisal (Rangkiang Mathematics Journal, 2024)
This research is motivated by students' ability to understand mathematical concepts, which is still relatively low. This research aims to determine the positive and significant influence of the Problem-Based Learning learning model on students' ability to understand mathematical concepts. This research method is quantitative research with a pre-experimental design research type with a one-group pretest-posttest design. The sampling technique used a saturated sampling technique with a sample of 21 students. The instruments used were concept understanding ability tests and observation sheets on implementing teacher learning and student activities. The research results show that students' understanding of mathematical concepts using the Problem-Based Learning learning model has increased significantly.